RURAL FUNERARY LANDSCAPES ON THE SYRIAN COAST DURING THE ROMAN AND BYZANTINE PERIODS: ARCHITECTURE, EPIGRAPHY, AND CULTURAL IDENTITY - Maha Ismail, (PEOPLE: International Journal of Social Sciences, 2025)
This paper investigates the funerary landscapes of rural settlements along the Syrian coast during the Roman and Byzantine periods. Spanning the 1st–6th centuries CE, lebanit examines how burial forms and mortuary rituals reflected broader transformations in social, religious, and cultural identity. Drawing on epigraphic evidence (Aliquot, 2010; Gatier, 2005), national archaeological surveys (Badawi 2010, 2015, 2016-2019), and the author’s own field documentation in the Jableh hinterland, the study develops a typology of rural tombs. It situates them in relation to settlements, agricultural installations, and sacred sites. Case studies from Khirbet al-Mirdesiya, Bishman, Barsoomah, Arab al-Milk, and al-Rahbiyya highlight the predominance of rock-cut tombs, the selective use of Greek funerary inscriptions by rural elites, and the gradual Christianization of mortuary space. By comparing these practices with funerary traditions in Lebanon and the Syrian Limestone Massif, the paper demonstrates both regional continuities and unique coastal developments. The analysis highlights how burial spaces were not passive residues, but rather active social and symbolic constructs. They encoded kinship, memory, and belief into the physical landscape, thereby offering a valuable lens into the cultural identity of rural communities in Late Antiquity.